The Universalization of Language Communication Values in Religious Community Harmony: The Case Study of Sundanese Islamic Society - Suherman, Ahmad (ASPENSI in Bandung, Indonesia, 2011)
ABSTRACT: This study is oriented to find out the potential spots that can enforce communication played by various religious inherent. It means that if there is harmonious or disharmonious condition in inter-religious community lives, such condition was based on the potential spot, which in this case is communication through religiosity language. The method used in this study is qualitative descriptive method with naturalistic approach; while data collecting technique is conducted through interview, observation, and documentary study. The subjects of this study are 13 cross-religion figures, which are assumed to know and experience directly the studied problem. From the findings, a number of dictions are inventarized, which can create or maintain the harmony of inter-religious community such as: (1) âAdilâ or Fair, (2) âAlhamdulillahâ or Thank God, (3) âAminâ or Trust, (4) âAssalamualaikumâ or Peace be Upon You, (5) âIkhlasâ or Sincere, (6) âIslahâ or Dispute Settlement at Peace and Quiet, (7) âMusyawarahâ or Agreement via Discussion, (8) âRahmatâ or Bless, and (9) âSilaturahmiâ or Good Relationship.KEY WORDS: Universalization, communication, good values, harmony and disharmony community, and Islamic/Arabic language.About the Author: Dr. Ahmad Suherman is Senior Lecturer at the Department of Arabic Language Education, Faculty of Art and Language Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. He can be reached at: h_asuherman@yahoo.co.idHow to cite this article? Suherman, Ahmad. (2011). âThe Universalization of Language Communication Values in Religious Community Harmony: The Case Study of Sundanese Islamic Societyâ in TAWARIKH: International Journal for Historical Studies, Vol.3(1) October, pp.77-94. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 2, 2011); Revised (September 5, 2011); and Published (October 28, 2011).